2015
DOI: 10.1103/physrevb.92.134409
|View full text |Cite
|
Sign up to set email alerts
|

Competing magnetic and structural states in multiferroicYMn2O5at high pressure

Abstract: The magnetic, structural, and vibrational properties of YMn 2 O 5 multiferroic have been studied by means of neutron, x-ray powder diffraction, and Raman spectroscopy at pressures up to 6 and 30 GPa, respectively. Application of high pressure, P > 1 GPa, leads to a gradual suppression of the commensurate and incommensurate antiferromagnetic (AFM) phases with a propagation vector q = (1/2,0,q z ∼1/4) and appearance of the commensurate AFM phase with q = (1/2,0,1/2). This observation is sharply contrasting to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 36 publications
(54 reference statements)
2
11
0
1
Order By: Relevance
“…strong anisotropy between the curve related to the lattice parameter a and those for b and c. The compressibility along the a direction at 9 GPa is twice that along the b and c directions (which are similar), indicating that the structure is softer along the a direction. Such behavior is observed for all the measured compounds, as well as for the Y, Bi and Ho compounds, as can be seen in the reports by Kozlenko et al (2015) and Grzechnik et al (2010). It is interesting to note that the a direction is the apical direction of the Mn 3+ O 5 pyramids.…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…strong anisotropy between the curve related to the lattice parameter a and those for b and c. The compressibility along the a direction at 9 GPa is twice that along the b and c directions (which are similar), indicating that the structure is softer along the a direction. Such behavior is observed for all the measured compounds, as well as for the Y, Bi and Ho compounds, as can be seen in the reports by Kozlenko et al (2015) and Grzechnik et al (2010). It is interesting to note that the a direction is the apical direction of the Mn 3+ O 5 pyramids.…”
Section: Figuresupporting
confidence: 78%
“…In these complex systems, the large effect of small variations in the interatomic distances and angles on the super-exchange integrals induces a strong dependence of the multiferroic properties on external factors. Indeed, an enhanced polarization has been observed under pressure (de la Cruz et al, 2006;Chaudhury et al, 2008) in the RMn 2 O 5 (R = Tb, Ho and Y) compounds and it has been associated with a new pressure-induced magnetic phase, recently shown by neutron measurements on Y (Deutsch et al, 2015;Kozlenko et al, 2015), Tb (Deutsch et al, 2018) and PrMn 2 O 5 (Peng et al, 2017). The dependence of the electric polarization of RMn 2 O 5 at ambient pressure as a function of the ionic radius of R 3+ .…”
Section: Introductionmentioning
confidence: 96%
“…But as shown in Fig. 6 for the Pr composition and as observed in Y, Bi and Ho 10,28 , the a lattice parameter strongly decreases with pressure. This induces a decrease of the angle involved in J 4 (from 132.5 at 0 GPa to 130.5 at 8 GPa) with increasing pressure.…”
supporting
confidence: 57%
“…In this paper, we address this question and pursue the idea that applying pressure is a good tool to unveil the mechanisms at the origin of these behaviors on a macroscopic scale [16,21] or microscopic one [22,23]. Previous neutron-diffraction studies on YMn 2 O 5 and PrMn 2 O 5 under high pressure have shown the onset of a pressure-induced commensurate phase (PCM), which appears at low pressure and progressively develops as pressure increases at the expense of both the ambient pressure CM and the ICM phases [22][23][24]. The PCM phase propagation vector k = ( 1 2 0 1 2 ) is the same as in BiMn 2 O 5 at ambient pressure.…”
Section: Introductionmentioning
confidence: 99%